Field redefinitions in classical field theory with some quantum perspectives - Criado, Juan Carlos; Jaeckel, Joerg; Spannowsky, Michael (Physical review, 2025)
In quantum field theories, field redefinitions are often employed to remove redundant operators in the Lagrangian, making calculations simpler and physics more evident. This technique requires some care regarding, among other things, the choice of observables, the range of applicability, and the appearance and disappearance of solutions of the equations of motion (EOM). Many of these issues can already be studied at the classical level, which is the focus of this work. We highlight the importance of selecting appropriate observables and initial/boundary conditions to ensure the physical invariance of solutions. A classical analog to the Lehmann-Symanzik-Zimmermann (LSZ) formula is presented, confirming that some observables remain independent of field variables without tracking redefinitions. Additionally, we address, with an example, the limitations of noninvertible field redefinitions, particularly with nonperturbative objects like solitons, and discuss their implications for classical and quantum field theories.